2021
DOI: 10.1038/s41598-021-96896-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of endangered Zhoushan cattle suggests its origin and the association of MC1R with black coat colour

Abstract: Zhoushan cattle are an endangered cattle breed in the Zhoushan islands in China. Since Zhoushan cattle have been bred in isolation, they show unique characteristics, such as dark black coat colour. However, no studies have been conducted on the genome of Zhoushan cattle. Here, we performed whole-genome sequencing of seven individuals of Zhoushan cattle and nine cattle in Wenling, geographically close to the Zhoushan islands. By integrating our data and publicly-available data, we found that Zhoushan cattle are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…With the development of the next-generation sequencing technology and the enrichment of re-sequencing databases, genome-wide genetic analysis plays an increasingly significant role in the investigation and selection of germplasm resources of landraces ( Shen et al, 2020 ; Jiang et al, 2021 ; Xia et al, 2021 ; Zhang et al, 2021 ). A recent study on Dengchuan cattle showed that Dengchuan cattle are a taurine–indicine mixed breed ( Foissac et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the next-generation sequencing technology and the enrichment of re-sequencing databases, genome-wide genetic analysis plays an increasingly significant role in the investigation and selection of germplasm resources of landraces ( Shen et al, 2020 ; Jiang et al, 2021 ; Xia et al, 2021 ; Zhang et al, 2021 ). A recent study on Dengchuan cattle showed that Dengchuan cattle are a taurine–indicine mixed breed ( Foissac et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have firmly established that the MC1R gene is a key player in UVR-induced tanning and DNA repair mechanisms [ 61 , 62 ]. It has been reported that the genetic variation of MC1R gene is associated with the pattern of hair coloration in domestic animals such as cattle, pigs, and chickens [ 63 , 64 , 65 ]. In particular, a recent study identified the MC1R gene in endangered Zhoushan cattle associated with their black coat color at the genomic level [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the genetic variation of MC1R gene is associated with the pattern of hair coloration in domestic animals such as cattle, pigs, and chickens [ 63 , 64 , 65 ]. In particular, a recent study identified the MC1R gene in endangered Zhoushan cattle associated with their black coat color at the genomic level [ 63 ]. Therefore, we speculate that the MC1R gene may be associated with melanin deposition in Bohai Black cattle, but its function needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Skin pigmentation is a complex trait. The genetic variants responsible for skin pigmentation have been broadly investigated in cattle (Dorshorst et al, 2015; Gutiérrez‐Gil et al, 2007; Jiang et al, 2021; Matsumoto et al, 2020; Schmutz & Dreger, 2013). Recently, the coat color in cattle has been manipulated using gene editing technique, though fundamentally epigenetics play a forefront role in regulating the color genes, particularly when the methylation event occurs at CpG islands (Laible et al, 2021).…”
Section: Discussionmentioning
confidence: 99%